(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Microneedling, or Percutaneous Collagen Induction (PCI), is a minimally invasive dermatological procedure utilized for skin rejuvenation and the treatment of various dermatological concerns. Despite its popularity, clinical protocols regarding optimal needle penetration depth—which directly correlates to the intensity of the wound-healing cascade and fibroblast activation—remain heterogeneous. This article reviews the clinical impact of varying microneedling depths on skin quality parameters, including wrinkle severity, dermal elasticity, pore size, and patient-reported outcomes.